Development Strategy for Palaes Village Mangrove Park Ecotourism as a Buffer Destination of the Likupang National Strategic Tourism Area - Kondoj, Telly Hetty Isye; Solang, Jeanlly Adri; Gumolili, Youdy Joseph Hendrik; Sendow, Deby Christiani; Lendo, Fresi Beatrix; Sahentumuwo, Yuliana M. (CV. Social Politic Genius (SIGn), 2025)
Palaes Village possesses significant mangrove ecotourism potential as a buffer destination for the Likupang National Strategic Tourism Area; however, its performance remains low. This study aims to formulate a sustainable ecotourism development strategy by identifying potential opportunities, analyzing strategic factors (SWOT), and developing a priority digital marketing strategy. A descriptive qualitative method was employed. Data were collected via observation, in-depth interviews with purposive informants, and documentation, then validated using triangulation. Data were analyzed using the SWOT framework, which was further developed by the 4A1I and CBET frameworks. The findings reveal a fundamental paradox. The destination possesses significant Strengths in Attraction and Amenities, including the availability of homestays and MSME Kiosks. However, these are nullified by critical structural Weaknesses. These Weaknesses are identified as a severe deficit in Accessibility (poor roads), a complete failure in Ancillary Services (promotion), and institutional fragility (governance). The development strategy must be CBET-based, striking a balance among the conservation, economic, and social pillars. Two priority strategies are recommended: infrastructure advocacy to improve Accessibility and the adoption of Digital Marketing, rebranding the destination as ‘Educative Ecotourism’.